THE EFFECT OF RADIATION ON THE INCIDENCE AND MORTALITY FROM SOLID CANCER IN EAST KAZAKHSTAN AND PAVLODAR REGIONS, KAZAKHSTAN - Akhanov, Ualsher (School of Medicine, 2023)
Semey (Semipalatinsk) Nuclear Test Site (SNTS) presents a substantive importance for interdisciplinary research in fields of radiology, radiation protection and environmental health. The potential effect of nuclear testing is a great concern for local population and health officials, especially given little evidence on the effect of low-dose ionizing radiation on human health. Despite the importance of evidence in collected from past cohorts, little is known about the effect of ionizing radiation on the population today. The present study attempts to explore potential effects of low-dose background ionizing radiation on the population health today. In particular, it attempts to explore whether alpha and beta particles, radon gas, as well as cesium (Cs 137), radium (Ra 226), thoron (Th 232), potassium (40 K) measured in soil, drinking water, and vegetation has a significant effect on the cumulative incidence and mortality attributed to lung, liver, stomach, esophagus, thyroid and breast carcinomas. Multivariate linear regression results indicate that only radon has a significant dose-distance relationship and can be associated with the SNTS (p = 0.042). Other radioactive elements and ionizing particle measurements are likely to be natural environmental radiation. Breast cancer incidence was associated with Th 232 (p = 0.031) and 40 K (p = 0.004), esophagus cancer incidence showed association with 40 K (p = 0.007), Ra 226 (p = 0.011), Cs 137 (p = 0.01). Ra 226 is also a statistically significant risk factor for thyroid cancer (p = 0.01). Unexpected associations were found on the effect of Ra 226 on lung and stomach cancer, unrelated to radon gas exposure. Further studies on individual level are needed to validate these findings
Keywords: Type of access: Restricted; Radiation; Solid Cancer; Pavlodar Regions